2010
DOI: 10.1163/016942410x507678
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tack of Pressure-Sensitive Adhesives (PSAs) at Different Temperatures

Abstract: Pressure-sensitive adhesives (PSAs) have applications in the fields of packaging, joining, wound care, and personal care. Depending on the application of the PSA, different performance tests are carried out when new products are developed or the quality of the existing products is checked. Tack is the property of an adhesive that enables it to form instant bond on the surface under light pressure. The tack of a PSA strongly depends on the way the bond is created. Parameters such as the bonded area, contact tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…PSAs experience a decrease in elastic and viscous moduli with increased temperature. [ 27 ] To evaluate this parameter for a treated VHB, the experiments under different annealing temperatures of −18, 20, and 40 °C were performed using the regular peeling test protocol. The samples are stored under each one of the aforementioned temperatures, but the peeling test was performed at 20 °C.…”
Section: Resultsmentioning
confidence: 99%
“…PSAs experience a decrease in elastic and viscous moduli with increased temperature. [ 27 ] To evaluate this parameter for a treated VHB, the experiments under different annealing temperatures of −18, 20, and 40 °C were performed using the regular peeling test protocol. The samples are stored under each one of the aforementioned temperatures, but the peeling test was performed at 20 °C.…”
Section: Resultsmentioning
confidence: 99%
“…In the realm of mechanical performance studies of PSAs, various investigations have provided insights into their behavior under different environmental and loading conditions. Chiang et al utilized rheological tests to evaluate the influence of frequency and temperature on the viscosity of PSAs, uncovering a pronounced temperature sensitivity 8 . Their findings indicated a sharp decline in viscoelastic properties when transitioning from high to low temperatures, and they noted that PSAs with higher elastic moduli do not consistently exhibit increased tack across varying temperature conditions and phase angles.…”
Section: Introductionmentioning
confidence: 99%
“…While EHA films showed some fibrillation but without clear detachment. Chiang et al ., have reported the rheological studies of three PSAs of different composition of low‐ and high‐molecular‐weight rosin ester along with dicyclopentadiene. They concluded that the sensitivity of high‐molecular‐weight rosin toward temperature‐dependent rheological properties was greater than that of low‐molecular‐weight compound; it was directly related to change in tack behavior.…”
Section: Introductionmentioning
confidence: 99%